THE IMPORTANCE OF ARTIFICIAL INTELLIGENCE IN THE DETECTION OF KIDNEY DISEASES MODERN APPROACHES AND PROSPECTS - Khalilov Hikmatulla Dilshod o`gly; Shatursunova Madina Abdujamilovna; Shukurov Umidjon Majid o`gly (Western European Studies, 2025)
Kidney diseases, especially chronic renal failure (CRF) and acute kidney injury (AKI), are one of the most important problems for the global healthcare system. Early detection and dynamic monitoring of these diseases allow improving outcomes and optimizing treatment strategies. Traditional diagnostic methods in many cases depend on the human factor, which increases the likelihood of error. The development of artificial intelligence (AI) technologies is creating opportunities for automation, accurate analysis, and data-based decision-making in medical diagnostics and disease prognosis. This article discusses AI-based methods for diagnosing kidney diseases, their advantages, limitations, and future prospects.
Keywords: artificial intelligence; kidney failure; neural networks